Investigation of factors affecting COVID-19 vaccine acceptance among communities of universities in the United Arab Emirates - Maisa El Gamal; Ayisha Siddiqua; Waheed Kareem Abdul; Badria H. Almurshidi; Fares M. Howari (Human Vaccines & Immunotherapeutics, 2022)
The COVID-19 pandemic affected the lives of people living across the world and the development of vaccines against SARS-CoV-2 is considered to be one of the most promising solutions to contain the COVID-19 pandemic. In several countries, we are witnessing hesitancy toward COVID-19 vaccines, which is a complex phenomenon influenced by a variety of factors. A cross-sectional study was performed to comprehensively investigate the impact of factors like demography, COVID-19 pandemic-induced behavior, and vaccine attitude on COVID-19 vaccine acceptance (VA) among communities of five different universities in the United Arab Emirates (UAE). To investigate the effect of demography and COVID-19 pandemic-induced behavioral factors, Analysis of Variance was perfomed. The effect of COVID-19 vaccine attitudes on COVID-19 VA was examined through partial least squares-structural equations modeling. The results of the study showed no difference among the population in accepting COVID-19 vaccines due to their demographic factors. The effect of pandemic-induced behavioral factors on COVID-19 VA suggested that the people of UAE accepted COVID-19 vaccines irrespective of the movement and travel restrictions imposed due to the pandemic. The results on the effect of vaccine attitudes on COVID-19 VA showed that vaccine benefit attitudes, safety concerns, and trust in health-care professionals (TrHP) were found to be significant factors in VA. Furthermore, TrHP was found to reduce the negative effect of safety concerns related to COVID-19 VA. The findings broadly highlight that COVID-19 VA in the UAE was not hampered by demographic factors and the pandemic-induced behavioral constraints. The study also showed that people with co-morbidities had lower level of COVID-19 VA than people with no co-morbidities. To improve COVID-19 VA, the perceived benefits with COVID-19 vaccine and TrHP must be enhanced and simultaneously safety concerns of the vaccines need to be addressed.